Nikolai Berdyaev’s metaphyscics of gender - Kroczak, Justyna (Hybris, 2014)
Nikolai Berdyaev is the well-know Russian religious philosopher. He is famous mostly for works about dignity and freedom of man. These deliberations seems to be the utter base of all his philosophy, which we can call personalism. From that point of view, metaphysics of gender is founded on the respect and the human dignity. Berdyaev’s philosophy is in this aspect dedicated to woman, her relations to man, nature and God. Berdyaev made these relations complicated and my objective in this article is to make them clearer.